Personalized practice dosages may improve motor learning in older adults compared to “standard of care” practice dosages: A randomized controlled trial - Olivier, Geneviève N.; Dibble, Leland E.; Paul, Serene S.; Lohse, Keith R.; Walter, Christopher S.; Marker, Ryan J.; Hayes, Heather A.; Foreman, K. Bo; Duff, Kevin; Schaefer, Sydney Y. (Frontiers in Rehabilitation Sciences, 2022)
Standard dosages of motor practice in clinical physical rehabilitation are insufficient to optimize motor learning, particularly for older patients who often learn at a slower rate than younger patients. Personalized practice dosing (i.e., practicing a task to or beyond one’s plateau in performance) may provide a clinically feasible method for determining a dose of practice that is both standardized and individualized, and may improve motor learning. The purpose of this study was to investigate whether personalized practice dosages (practice to plateau [PtP] and overpractice [OVP]) improve retention and transfer of a motor task, compared to low dose [LD] practice that mimics standard clinical dosages. In this pilot randomized controlled trial (NCT02898701, clinicaltrials.gov), community-dwelling older adults (n=41, 25 female, mean age 68.9 years) with a range of balance ability performed a standing serial reaction time task in which they stepped to specific targets. Presented stimuli included random sequences and a blinded repeating sequence. Participants were randomly assigned to one of three groups: LD (n=15, 6 practice trials equaling 144 steps), PtP (n=14, practice until reaching an estimated personal plateau in performance), or OVP (n=12, practice 100% more trials after reaching an estimated plateau in performance). Measures of task-specific learning (i.e., faster speed on retention tests) and transfer of learning were performed after 2-4 days of no practice. Learning of the random sequence was greater for the OVP group compared to the LD group (p=.020).The OVP (p=.004) and PtP (p=.010) groups learned the repeated sequence more than the LD group, although the number of practice trials across groups more strongly predicted learning (p=0.020) than did group assignment (OVP vs. PtP, p=0.270). No group effect was observed for transfer, although significant transfer was observed in this study as a whole (p<.001). Overall, high and personalized dosages of postural training were well-tolerated by older adults, suggesting that this approach is clinically feasible. Practicing well beyond standard dosages also improved motor learning. Further research should determine the clinical benefit of this personalized approach, and if one of the personalized approaches (PtP vs. OVP) is more beneficial than the other for older patients.